Observatório: por uma materialidade da imagem na arte - Maria Elisa Martins Campos do Amaral (2011)
Having, as main focus, the perception of the image materiality, this research tries to explore the space where image production is settled within the plastic arts, joining different procedures going from thesimple nature observation and the use it makes of the technological, analogical and digital resources, always aiming to make evident the touchtability of the image, its contact and experimentation power.The initial assumption emerging all over the text is the individual fascination to reach the image, to see and touch it in order to feel its matter. This assumption brings with it the recognition of the importanceof the individual own body as the first step for the manifestation of image perception and constitution which act one over the other, producing different repercussions in each individual. Starting from thisassumption (BEING image), the research is unfolded in reflections associated to the quotidian image presence and more specifically in the art domain and for this reason this is the privileged subject of thisnarrative.Being part of the theoretical plan which comes from the artistic practice, the dimensions of the approach referring to image materiality are developed therefore from the act of doing itself. In first place, after having been inspired by the disclosure of water surface as a local of image reception and reflection, has resulted in a study about the act of observation, yet exploring shades and lights, which are always available resources to capture images. The research goes on afterwards on the different ways of capturing, which has in photography its maximum expression. Using examples which are not only restricted to the universe of art, it has been developed the organization of a wide repertory ofimages and situations which rends problematic the construction of images, its handling and transformation into art, as well as its interaction with the public. Therefore, to use and to abuse of images means a great spectrum which comes from the appropriation, going through dispersion and reaching the dilaceration of the image in a flow which embodies multiple senses. Finally, to inhabit the images in instances ratified by experience, permits a reflection which search about the image conditionas much as spatial and environmental reality linked to the immersion and to the landscape as well as for X the approach on the perceptible transformation of the contemporary human being sensitiveness andon the art placement as a space for proposals and displacements.There are explicit in the research three specific and integrated speeches: the speech of images assembled in groups which start the chapters; the experience reports dedicated to the development of the plastic work, also responsible for the different questions for reflection; the theoretical approach supported by concepts that show to be pertinent to the universe of the contemporary production. The association of these three speeches seeks to present the multiplicity of aspects in this particular challenge which is to create a space propitious to the approach on the image materiality in art which, we know, will never run out.